Survival of south african women with breast cancer receiving anti-retroviral therapy for HIV. (October 2021) - Phakathi, Boitumelo; Nietz, Sarah; Cubasch, Herbert; Dickens, Caroline; Dix-Peek, Therese; Joffe, Maureen; Neugut, Alfred I.; Jacobson, Judith; Duarte, Raquel; Ruff, Paul
Abstract: Purpose: Breast cancer outcomes in sub-Saharan Africa is reported to be poor, with an estimated five-year survival of 50% when compared to almost 90% in high-income countries. Although several studies have looked at the effect of HIV in breast cancer survival, the effect of ARTs has not been well elucidated. Methods: All females newly diagnosed with invasive breast cancer from May 2015–September 2017 at Charlotte Maxeke Johannesburg Academic and Chris Hani Baragwanath Academic Hospital were enrolled. We analysed overall survival and disease-free survival, comparing HIV positive and negative patients. Kaplan-Meier survival curves were generated with p-values calculated using a log-rank test of equality while hazard ratios and their 95% confidence intervals (CIs) were estimated using Cox regression models. Results: Of 1019 patients enrolled, 22% were HIV positive. The overall survival (95% CI) was 53.5% (50.1–56.7%) with a disease-free survival of 55.8% (52.1–59.3) after 4 years of follow up. HIV infection was associated with worse overall survival (HR (95% CI): 1.50 (1.22–1.85), p < 0.001) and disease-free survival (OR (95% CI):2.63 (1.71–4.03), p < 0.001), especially among those not on ART at the time of breast cancer diagnosis. Advanced stage of the disease and hormone-receptor negative breast cancer subtypes were also associated with poor survival. Conclusion: HIV infection was associated with worse overall and disease-free survival. HIV patients on ARTs had favourable overall and disease-free survival and with ARTs now being made accessible to all the outcome of women with HIV and breast cancer is expected to improve. Highlights: 22% of participants were HIV positive. The 4 years overall survival was 53.5%. The 4 years disease-free survival was 55.8%. HIV infection was associated with poor overall and disease-free survival. ART use was associated with better overall and disease-free survival.